Pengaturan Waktu Panen dan Pemupukan Nitrogen Tanaman Utama Terhadap Pertumbuhan dan Hasil Ratun Padi pada Lahan Pasang Surut: Pengaturan Waktu Panen dan Pemupukan Nitrogen Tanaman Utama Terhadap Pertumbuhan dan Hasil Ratun Padi pada Lahan Pasang Surut - Gribaldi Gribaldi; Nurlaili Nurlaili; Iqbal Effendy (Universitas Bangka Belitung, 2020)
Rice cultivation with a ratoon system is one of the efforts to increase rice production in tidal land. This study aims to determine the effect of harvest time and nitrogen fertilization of the main plant on the growth and yield of ratoon rice in tidal swampland. This study was conducted in the Experimental Field of Banyuasin District Agriculture Office in Tanjung Lago Regency. The design used in this study was the Split Plot Design which was repeated three times. The Main Plots: Fertilization N (N) consists of N1;½ dose at planting + ½ dose of primordia phase, N2; 1/3 dose at planting + 1/3 dose at primordial phase + 1/3 dose at harvest, and N3; 1/3 dose at planting + 1/3 dose at primordia phase+ 1/6 dose at harvest +1/6 dose at 21 days after harvest.Plot: Harvest time (W) consists of W1; the main crop is harvested 5 days before 100% ripening, W2; main crop is harvested when 100% ripening, and W3; the main crop is harvested 5 days after 100% ripening. The results showed that the harvest time and N fertilizer of the main plants affected the growth and yield of ratoon rice in tidal land. Treatment of harvest time 5 days before 100% ripening and N fertilization has given 1/3 dose at planting + 1/3 dose of primordia phase +1/3 dose at harvest, tended to show higher growth and yields of ratoon rice than other treatments, that is 2.06 tons/ha or 54.2 percent compared to the main crop.